2009
DOI: 10.1007/s10734-009-9246-5
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to studying in higher education Portuguese students: a Portuguese version of the approaches and study skills inventory for students

Abstract: This paper examines the validity of the Approaches and Study Skills Inventory for Students-short version (ASSIST; Tait et al. in Improving student learning: Improving students as learners, 1998), to be used with Portuguese undergraduate students. The ASSIST was administrated to 566 students, in order to analyse a Portuguese version of this inventory. Exploratory factor analysis (principal axis factor analysis followed by direct oblimin rotation) reproduced the three main factors that correspond to the original… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
49
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 31 publications
13
49
0
4
Order By: Relevance
“…The instrument has a proposed structure, based on theory and research, where the items are organized into three main scales. These scales are commonly referred to as the deep, strategic, and surface approaches to studying (Tait et al, 1998), and previous research has uniformly confirmed the three-factor structure of the ASSIST (Byrne et al, 2004;Diseth, 2001;Entwistle, Tait, & McCune, 2000;Kreber, 2003;Richardson et al, 2005;Valadas et al, 2010). In the present sample, the internal consistencies of the full-length scales were 0.81 (deep approach), 0.80 (strategic approach), and 0.77 (surface approach).…”
Section: Approaches To Studyingsupporting
confidence: 74%
See 3 more Smart Citations
“…The instrument has a proposed structure, based on theory and research, where the items are organized into three main scales. These scales are commonly referred to as the deep, strategic, and surface approaches to studying (Tait et al, 1998), and previous research has uniformly confirmed the three-factor structure of the ASSIST (Byrne et al, 2004;Diseth, 2001;Entwistle, Tait, & McCune, 2000;Kreber, 2003;Richardson et al, 2005;Valadas et al, 2010). In the present sample, the internal consistencies of the full-length scales were 0.81 (deep approach), 0.80 (strategic approach), and 0.77 (surface approach).…”
Section: Approaches To Studyingsupporting
confidence: 74%
“…The items comprise three main scales (the deep, surface, and strategic approaches to studying), each of which is comprised by four to five subscales. Factor analytic studies across a range of disciplines have consistently reproduced the theoretically proposed threefactor structure (Byrne, Flood, & Willis, 2004;Diseth, 2001;Kreber, 2003;Richardson, 2005Richardson, , 2010Valadas, Goncalves, & Faísca, 2010), and the same structure was also recently found in a cross-cultural sample of occupational therapy students (Bonsaksen, Småstuen, et al, 2017). Internal consistency has been found to be high for the main scales, while it has been deemed acceptable or in the lower range for the subscales (Ballantine, Duff, & Larres, 2008;Bonsaksen, Småstuen, et al, 2017;Reid, Duvall, & Evans, 2005;Reid, Evans, & Duvall, 2012;Richardson, 2010;Richardson, Gamborg, & Hammerberg, 2005;Valadas et al, 2010).…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…Previous research reports that the ASSIST produces satisfactory reliability coefficients when administered to samples of North-American and European students Flood & Wilson, 2008;Tait & Entwistle, 1996), with internal consistency ranging from 0.70 (Diseth, 2001) to 0.83 (Byrne et al, 2004) for the surface approach; between 0.81 (Ballantine, Duff, & Larres, 2008;Diseth, 2001) and 0.85 (Ballantine et al, 2008) for the deep approach; and between 0.81 (Diseth, 2001) and 0.88 (Ballantine et al, 2008) for the strategic approach. A previous study with Portuguese college students reported coefficients of 0.79 for the surface approach, 0.81 for the deep approach, and 0.83 for the strategic approach (Valadas, Gonçalves, & Faisca, 2010).…”
Section: Study Timementioning
confidence: 90%